The HNPCC associated MSH2*1906G→C founder mutation probably originated between 1440 CE and 1715 CE in the Ashkenazi Jewish population. Issue 10 (30th September 2005) - Sun, S; Greenwood, C M T; Thiffault, I; Hamel, N; Chong, G; Foulkes, W D
Abstract : The MSH2*1906G→C mutation was recently shown to be a rare yet highly penetrant mutation leading to colorectal cancer. The mutation was only found among Ashkenazi Jewish individuals and lies on an extended haplotype that is common in that population. This study determined that the mutation probably arose between 11 and 22 generations ago, during the time when the Ashkenazim were living in eastern Europe.